Microalgae living sensor for metal ion detection with nanocavity-enhanced photoelectrochemistry - Roxby, Daniel N. (2022)
Metal ions are known to play various roles in living organisms; therefore, the detection of metal ions in water resources is essential for monitoring health and environmental conditions. In contrast to artificially fabricated materials and devices, biological-friendly materials such as microalgae have been explored for detecting toxic chemicals by employing fluorescence emissions and biophotovoltaic fuel cells. However, complicated fabrication, long measurement time, and low sensitivity remain the greatest challenge due to the minimal amount of bioelectricity generated from whole-cell microalgae. Herein we report the novel concept of a microalgae living biosensor by enhancing photocurrent through nanocavities formed between copper (Cu) nanoparticles and the Cu-electrode beneath. The strong energy coupling between plasmon cavity modes and excited photosynthetic fluorescence from Chlorella demonstrated that photoelectrical efficiency could be significantly amplified by more than two orders of magnitude through nanocavity confinement. Simulation results reveal that substantial near-field enhancements could help confine the electric field to the electrodes. Finally, the microalgae sensor was exploited to detect various light and heavy metal ions with a breakthrough detection limit of 50 nM. This study is envisioned to provide inspirational insights on nanocavity-enhanced electrochemistry, opening new routes for biochemical detection, water monitoring, and sustainable optoelectronics.